The risk factors for postpartum depression: A population‐based study - Silverman, Michael E.; Reichenberg, Abraham; Savitz, David A.; Cnattingius, Sven; Lichtenstein, Paul; Hultman, Christina M.; Larsson, Henrik; Sandin, Sven (Depression and anxiety, 2017)
Background Postpartum depression (PPD) can result in negative personal and child developmental outcomes. Only a few large population‐based studies of PPD have used clinical diagnoses of depression and no study has examined how a maternal depression history interacts with known risk factors. The objective of this study was to examine the impact of a depression history on PPD and pre‐ and perinatal risk factors. Methods A nationwide prospective cohort study of all women with live singleton births in Sweden from 1997 through 2008 was conducted. Relative risk (RR) of clinical depression within the first year postpartum and two‐sided 95% confidence intervals were estimated. Results The RR of PPD in women with a history of depression was estimated at 21.03 (confidence interval: 19.72–22.42), compared to those without. Among all women, PPD risk increased with advanced age (1.25 (1.13–1.37)) and gestational diabetes (1.70 (1.36–2.13)). Among women with a history of depression, pregestational diabetes (1.49 (1.01–2.21)) and mild preterm delivery also increased risk (1.20 (1.06–1.36)). Among women with no depression history, young age (2.14 (1.79–2.57)), undergoing instrument‐assisted (1.23 (1.09–1.38)) or cesarean (1.64(1.07–2.50)) delivery, and moderate preterm delivery increased risk (1.36 (1.05–1.75)). Rates of PPD decreased considerably after the first postpartum month (RR = 0.27). Conclusion In the largest population‐based study to date, the risk of PPD was more than 20 times higher for women with a depression history, compared to women without. Gestational diabetes was independently associated with a modestly increased PPD risk. Maternal depression history also had a modifying effect on pre‐ and perinatal PPD risk factors.